Website-Based Application Design for Drug Needs (RKO) Using the Consumption Method at Glagah Public Health Center - Nizami, Ahmad Alfian; Lusiani, Titik; Wardhanie, Ayouvi Poerna (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2021)
Puskesmas Glagah is a health service facility located at Jalan Raya Glagah, No. 61, Kepuh, Bapuh Baru, Lamongan Regency. Drug demand planning has a big impact on the availability of drugs in puskesmas. There is a method that can help health centers plan their drug needs for the coming year, this method is the consumption method. The consumption method is based on pharmaceutical consumption data so it is often used as the most accurate estimate in pharmaceutical supply planning. During its development at the Glagah Puskesmas there were problems, especially in the planning of drug stock supplies. The stockout occurred because in planning the RKO was not monitored and only approved requests from each department of poly, when policemen submitted requests for drugs, they were immediately received by the pharmacy department without monitoring how many drugs were needed in a certain period, causing the business process at the puskesmas to be hampered.Based on these problems, a system that can calculate drug planning is needed so that it can help the health center in minimizing the losses caused by drug vacancies. The results showed that the consumption method was successfully applied to the planning function of drug needs with a comparison of the data for the last 3 years that went well and allowed the health center to control the availability of drug stocks.